P04.51 TERT promoter mutation-driven TERT activation is mediated by ETS1 in BRAF V600E mutated glioma. (19th September 2018) - Gabler, L; Gojo, J; Lötsch, D; Kirchhofer, D; van Schoonhoven, S; Stojanovic, M; Schmidt, H M; Ensle, D; Czech, T; Haberler, C; Slavc, I; Spiegl-Kreinecker, S; et al.
Abstract: Background: Malignancies of the central nervous system are characterized by the highest lethality among pediatric tumors. Interestingly, brain tumors such as pleomorphic xanthoastrocytoma or epithelioid glioblastoma often harbor genomic BRAF alterations (e.g. V600E) leading to hyperactivation of the MAPK pathway. Additionally, activating point mutations in the TERT promoter have been described as the most frequent genomic alterations in certain glioma subtypes. However, a crosstalk between BRAF and TERT promoter mutations has not been established so far in these tumors. Material and Methods: Herein, we interrogated the impact of BRAF mutations on TERT promoter activity. We have applied cell viability and clonogenicity assays and explored TERT promoter activity by luciferase reporter assays. Gene expression and downstream signaling upon MAPK pathway inhibition or siRNA knock-down were characterized by use of q-RT-PCR and Western blots, respectively. Results: In a curated dataset of 103 BRAF V600E mutated glioma originating from publicly available data sets, we found BRAF and TERT promoter mutated glioma to be significantly enriched in high grade glioma as compared to low grade glioma. Based on this finding, a panel of primary glioma cell lines with differential BRAF and TERT promoter mutation status was established and treated with MAPK pathway inhibitors. Remarkably, TERT expression as well as TERT promoter activity was only downregulated in tumors with both BRAF V600E and TERT promoter mutations, while TERT expression was undetectable in only BRAF V600E mutated cells. As TERT promoter mutations are known to generate de novo ETS-binding sites, we thought to investigate the role of ETS factors in further detail. ETS1 activation and gene expression were significantly downregulated by MAPK inhibitors in BRAF V600E and TERT promoter mutated tumors. In contrast, BRAF inhibition was insufficient to block ETS1 expression in a TERT promoter wildtype background. Intriguingly, knock-down experiments proved the functional role of ETS1 as bridge molecule interconnecting MAPK pathway and telomerase reactivation in double-mutant tumors. Accordingly, tumor cells harboring both mutations were significantly more sensitive towards ETS factor-targeting therapy as compared to cell models of the other genotypes. Conclusion: In conclusion, our data suggest that concomitant BRAF V600E and TERT promoter mutations synergistically drive tumor aggressiveness by promoting cancer cell proliferation and immortalization. ETS1 represents the major driver functionally linking these two highly abundant genomic alterations and might represent a promising therapeutic target specifically in double-mutant glioma. Support: This project was supported by Austrian Science Fund FWF (project number: P30105 to WB) and by Fellinger Krebsforschung (to JG).